APPLICATION OF CHEMOTHERAPY MONITORING IN CHILDREN WITH CANCER IN THE ASOKA BARAT WARD OF DR. SARDJITO GENERAL HOSPITAL - Alvina Nur Khaylila; Sumarti Endah Purnamaningsih Maria Margaretha (Jurnal Kesehatan Karya Husada, 2026)
Background: Childhood cancer is an abnormal and uncontrolled growth of cells that attacks growth and development in children. Chemotherapy is one of the cancer treatments that causes side effects, such as nausea, vomiting, and fatigue. Monitoring at the chemotherapy stage (pre, intra, and post) is carried out to ensure safety and comfort during therapy. Objective: To find out the results of chemotherapy monitoring in children with cancer in the West Asoka Room of Dr. Sardjito Hospital. Methods: using a descriptive case study method of four children undergoing chemotherapy with the drug Etoposid. Monitoring was carried out in three stages, namely pre, intra, and post chemotherapy. Data was collected through observation, interviews, and documentation studies using monitoring sheets set by the hospital. Results: Of the four respondents who underwent Etoposid chemotherapy, three children (75%) experienced nausea, while one child (25%) experienced no side effects. Side effects such as shock, allergies, or seizures were not found. Conclusion: From the monitoring results, three out of four children experienced nausea. Monitoring provides benefits in maintaining safety during chemotherapy.